Study of the reproductive toxicity of probiotic strains on laboratory animals. Issue 1 (February 2021) - Skvortsov, Evgeny; Mukhammadiev, Rishat; Mukhammadiev, Rinat; Valiullin, Lenar; Rud, Vasily; Glinushkin, rew
Abstract: The objective of this study was to determine the effect of probiotic preparations contained Bacillus subtilis 10 9 CFU / ml, Propionibacterium 10 7 CFU / ml, Lactobacillus plantarum 10 7 CFU / ml on the physiological state, reproductive functions and the mortality rate of white rats and their offspring. The results of the analysis of the reproductive toxicity of the suspension of strains of probiotics and producers of prebiotics showed that long-term oral administration of the studied doses did not lead to a decrease in the reproductive function of laboratory animals during the experimental period, corresponded to the norm and did not differ significantly from the indicators of the control group. Based on the results obtained, the investigated form of the probiotic can be classified as a drug of low toxicity for reproductive function and, in accordance with GOST 12.1.007-76, referred to the IV hazard class.